2018
DOI: 10.3390/polym10050522
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Silicone Rubbers as Sealing Materials for Proton Exchange Membrane Fuel Cells under Temperature Cycling

Abstract: Gaskets are compressed in proton exchange membrane fuel cells (PEMFCs) to keep fuel, oxidant and coolant within their respective regions and are very important for sealing and maintaining electrochemical performance of fuel cells during their long-term operation. It has been proved that the gas leakage caused by the failure of the gaskets following long-term operation is one of the main reasons for PEMFC performance degradation. In this work, degradation of silicone rubbers, the potential gasket materials for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Additionally, EPDM polymers are nonpolar and, hence, have good resistance to water and aqueous solutions along with low crystallinity and, hence, can accept high loading of fillers to obtain adequate mechanical properties [167]. EPDM generally has good durability in the long run in addition to being acid resistant [168,169]. An EPDM rubber polymer contains ethylene, propylene, and a diene monomer that gives a site of unsaturation for crosslinking.…”
Section: Ethylene-propylene-diene Monomer (Epdm)mentioning
confidence: 99%
“…Additionally, EPDM polymers are nonpolar and, hence, have good resistance to water and aqueous solutions along with low crystallinity and, hence, can accept high loading of fillers to obtain adequate mechanical properties [167]. EPDM generally has good durability in the long run in addition to being acid resistant [168,169]. An EPDM rubber polymer contains ethylene, propylene, and a diene monomer that gives a site of unsaturation for crosslinking.…”
Section: Ethylene-propylene-diene Monomer (Epdm)mentioning
confidence: 99%
“…Additionally, the fault energy also increases with ageing duration, and therefore ethylene and acetylene are observed in significant amounts only on day 45. The oxidation of insulative silicone rubber could result in carbon dioxide as one of its byproducts [28]. Consequently, the amount of CO 2 dissolved in Si samples is higher than in Oil samples.…”
Section: Dga Of Sample Type Simentioning
confidence: 99%
“…The degradation of silicone rubbers, the potential gasket materials for PEMFC, was investigated in the simulated PEMFC environment solution, weak acid solution, de-ionized water, and air, respectively, under alternating temperature cycling from 20 to 90 • C. The results showed that with the increase in temperature cycles, the hardness of the samples increased and the weight of the samples decreased gradually. Meanwhile, attenuated total reflection Fourier transform infrared spectrometer (ATR-FTIR) results demonstrated that the surface chemistry changed via de-crosslinking and chain scission in the backbone due to the exposure of samples to the environments over time under alternating temperature cycles [9]. The degradation of silicone rubbers, as potential gasket materials for PEMFC, was investigated in different cold-start processes ranging from −10 to 90 • C and −20 to 90 • C. It was found that the hardness of the silicone rubbers increased, and their weight gradually decreased with increasing number of temperature cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that with the increase in temperature cycles, the hardness of the samples increased and the weight of the samples decreased gradually. Meanwhile, attenuated total reflection Fourier transform infrared spectrometer (ATR‐FTIR) results demonstrated that the surface chemistry changed via de‐crosslinking and chain scission in the backbone due to the exposure of samples to the environments over time under alternating temperature cycles [9]. The degradation of silicone rubbers, as potential gasket materials for PEMFC, was investigated in different cold‐start processes ranging from −10 to 90°C and −20 to 90°C.…”
Section: Introductionmentioning
confidence: 99%